Pengaruh Keharmonisan Orangtua Dalam Keluarga Terhadap Pertumbuhan Rohani Remaja Usia ( 15-17 ) di GKPS Siantar Timur - Siregar, Nurliani; Nainggolan, Justinos (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2024)
Based on the problems that occurred in research entitled "The Influence of Parental Harmony on the Spiritual Growth of Adolescents aged (15-17 years) at the Simalungun Protestant Christian Church (GKPS)" East Siantar, Jalan Siantar Timur, Siopat Suhu Village, East Siantar District, Pematang Siantar, North Sumatra. A church synod that is Lutheran and is also a member of the PGI. The type and method of research used is quantitative research with descriptive methods. After carrying out a data normality test on data X and data Y as one of the requirements for the following data analysis, it turns out that data X and data Y each have a normal distribution. Data normality testing has been carried out using the Chi Square (X²) table formula with a real level = 0.05, namely for data This means that data X (Harmony of Parents in the Family) is in a normal distribution or data X comes from a normal distribution. For Y data (Teenager Spiritual Growth at GKPS Namorambe) 〖Y²〗_count = -29.738 while 〖Y²〗_tabel= 9.49 means that Y data (Teenager Spiritual Growth at East Siantar GKPS) is in a normal distribution or Y data comes from a distributed sample normal. a new template / format as well as a manuscript / article template used for journalwriting published in the Journal of Management of Elementary, Middle and Higher Education.The manuscript begins with the Article Title, Author Name, Author Affiliation Address and email correspondence followed by a 200-250 word abstract. Especially for Abstract, the text is written with a left margin of 3.5 cm, a right margin of 2.5 cm, top and bottom 2.5 cm each with a font size of Size 10 pt and the fonts of Times New Roman, Bold and one spacing between lines. Abstracts are made in Indonesian or English. If the article is in English, then the abstract must be written in English only. The Abstract section must contain the core of the problem to be presented, the method of solving it, and the scientific findings obtained and the conclusions. Abstracts for each language may only be written in one paragraph with one column format.